2024
DOI: 10.1126/sciimmunol.adf2223
|View full text |Cite
|
Sign up to set email alerts
|

Beyond T cell exhaustion: TIM-3 regulation of myeloid cells

Karen O. Dixon,
Gonzalo Fernandez Lahore,
Vijay K. Kuchroo

Abstract: T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3) is an important immune checkpoint molecule initially identified as a marker of IFN-γ–producing CD4 + and CD8 + T cells. Since then, our understanding of its role in immune responses has significantly expanded. Here, we review emerging evidence demonstrating unexpected roles for TIM-3 as a key regulator of myeloid cell function, in addition to recent work establishing TIM-3 as a delineator of term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…We were surprised to observe that β-catenin active cDC1s (cDC1s with active β-catenin, from CD11c-β-catenin active mice) exhibited elevated expression of Tim-3 (Figure 1) in contrast to unchanged or reduced expression of other inhibitory molecules including PD-L1 and Lag3 (Figure S2). The anti-Tim-3 antibody has been tested clinically as a new addition to immune checkpoint blockade immunotherapies [57][58][59], although the mechanism underlying how Tim-3 blockade achieves its anti-tumor effects is not well understood [60]. Of note, we and others have shown that multiple tumors induce up-regulation/activation of β-catenin in DCs, including tumor-infiltrated DCs to restrain anti-tumor CD8 T cell responses [20,21,23,24], raising the intriguing scenario that tumors might exploit the β-catenin/Tim-3 pathway in DCs to suppress anti-tumor CD8 T cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We were surprised to observe that β-catenin active cDC1s (cDC1s with active β-catenin, from CD11c-β-catenin active mice) exhibited elevated expression of Tim-3 (Figure 1) in contrast to unchanged or reduced expression of other inhibitory molecules including PD-L1 and Lag3 (Figure S2). The anti-Tim-3 antibody has been tested clinically as a new addition to immune checkpoint blockade immunotherapies [57][58][59], although the mechanism underlying how Tim-3 blockade achieves its anti-tumor effects is not well understood [60]. Of note, we and others have shown that multiple tumors induce up-regulation/activation of β-catenin in DCs, including tumor-infiltrated DCs to restrain anti-tumor CD8 T cell responses [20,21,23,24], raising the intriguing scenario that tumors might exploit the β-catenin/Tim-3 pathway in DCs to suppress anti-tumor CD8 T cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, T cell activation and suppression of the negative regulation of TIM-3 lead to enhanced effector activity of T cells ( Figure 4A ). However, when TIM-3 binds its ligand, Bat-3 dissociates after phosphorylation of Y256/Y263 106 , thus allowing Fyn, another Src kinase, to bind TIM-3. Lck is inactivated, and ZAP70 function is downregulated, thereby ultimately inducing T cell exhaustion 107 .…”
Section: Emerging Immune Checkpoint Inhibitorsmentioning
confidence: 99%